Teachers' acceptance of technologies for 4IR adoption: implementation of the UTAUT model - Ab Jalil, Habibah; Rajakumar, Manjula; Zaremohzzabieh, Zeinab (Society for Research and Knowledge Management, 2022)
Education departments all around the globe are working to increase the extent to which teachers adopt innovative technology, in order to scale up pedagogical innovation that uses new technologies. However, only a few studies have been done on the adoption and use of these tools for teaching by instructors in non-Western contexts. Therefore, the objective of this study was to examine teachers’ behavior intention to adopt and use Industry 4.0 (IR4.0) technologies in Malaysia, in accordance with the unified theory of acceptance and the use of technology (UTAUT) model. A questionnaire was employed to acquire data from a randomly selected sample of 62 primary school teachers in Malaysia. The findings reveal that only two variables (namely, the facilitating conditions, and social influence variables) have a direct impact on the behavior intention of Malaysian primary school teachers to use IR4.0 technologies. Neither effort expectancy nor performance expectancy have an impact on the intention to use these technologies. The study concludes with a set of recommendations for improving policy and research on teachers’ use of IR4 for education. This work demonstrates how the findings may assist primary school teachers to improve their understanding of 4IR adoption, and provides valuable suggestions for 4IR scholars, producers, and users.